Russia’s New Capacity-based Renewable Energy Support Scheme : An Analysis of Decree No. 449 - International Finance Corporation (Moscow, 2017)
On 28 May, 2013, the Government of the Russian Federation adopted decree no. 449 on the mechanism for the promotion of renewable energy (RE) on the wholesale electricity and capacity market. Decree no. 449 integrates support for renewable energy sources for electricity (RES-E) into the capacity market. This is a very different approach to that applied in most of the existing support mechanisms in other countries, where RES-E is promoted on the basis of the electricity output (MWh) rather than the installed capacity (MW or MW per month) of RE installations. Promoting RES-E through the capacity market is a way for the Russian authorities to overcome some of the legal and technical challenges faced by previous support initiatives and, importantly, to control the costs of RE. This approach fits well with the specific regulatory architecture of the Russian wholesale electricity market, which comprises both an energy and capacity segment. This report introduces Russia’s new capacity-based scheme and examines how the Russian authorities have integrated the variability of RE sources into the regulation of capacity supply. This analysis will highlight the risk of legal uncertainty affecting the business case for RE investors under the capacity-based scheme. For more publications on IFC Sustainability please visit www.ifc.org/sustainabilitypublications.